A novel indel in exon 9 of APC upregulates a ‘skip exon 9' isoform and causes very severe familial adenomatous polyposis - Cheah, Peh Yean (Nature Publishing Group, 2014)
Germline mutation in the adenomatous polyposis coli (APC) gene causes the majority (80%) of familial adenomatous polyposis (FAP), an autosomal dominantly inherited form of colorectal cancer (CRC). Mutation in 5′end of exon 9 of APC usually results in an attenuated form of FAP (aFAP), characterized by later age of onset and fewer polyps. The presence of exon 9a, an in-frame isoform with exon 8 spliced to 3′end of exon 9, modulates any deleterious effect of the mutation. A third lowly expressed isoform that completely skips exon 9 is present in both healthy individuals and FAP patients. We report here an interesting case of a proband with an APC mutation in 5′end of exon 9 that presented with six synchronous advanced CRCs at age 37. The novel insertion–deletion (indel) at codon 409, c.1226-1229delTTTTinsAAA, caused upregulation of the ‘skip exon 9' isoform, r934-1312del, resulting in a premature stop codon at exon 10 and a truncated protein that removed all of the β-catenin (CTNNB1) binding motifs, thus activating the downstream T-cell transcription factor (Tcf) pathway. Exon 9a isoform was concomitantly downregulated. This finding emphasizes the necessity of examining the various isoforms of exon 9 to avoid clinical mismanagement and counseling based on just the mutation site by genomic DNA sequencing alone.